The State and Politics in Japan - Neary, Ian (Polity, 2019)
"In this fully revised and updated second edition of his classic text, Ian Neary explores the dynamics of democracy in Japan, introducing the key institutions, developments and actors in its politics from the end of the Second World War to the present day."--Provided by publisher.